2022
DOI: 10.1371/journal.pone.0274208
|View full text |Cite
|
Sign up to set email alerts
|

Identification of circulating metabolites associated with wooden breast and white striping

Abstract: Current diagnostic methods for wooden breast and white striping, common breast muscle myopathies of modern commercial broiler chickens, rely on subjective examinations of the pectoralis major muscle, time-consuming microscopy, or expensive imaging technologies. Further research on these disorders would benefit from more quantitative and objective measures of disease severity that can be used in live birds. To this end, we utilized untargeted metabolomics alongside two statistical approaches to evaluate plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…The results of the PLS-DA analysis in the current study imply that WB and WS do not share a similar metabolic profile, but rather, express different changes in metabolite profiles, even if pathophysiological similarities might occur between the two diseases. Our results also imply that the metabolomics profile can be used to differentiate the two groups, in line with observations in the literature [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of the PLS-DA analysis in the current study imply that WB and WS do not share a similar metabolic profile, but rather, express different changes in metabolite profiles, even if pathophysiological similarities might occur between the two diseases. Our results also imply that the metabolomics profile can be used to differentiate the two groups, in line with observations in the literature [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…The rate of anserine synthesis in skeletal muscle is dependent on the amount of circulating beta-alanine. In line with these findings, a recently published article on metabolomics in WB-affected birds indicated that 3-methyl-histidine was the top metabolite being affected in plasma, with eight more metabolites involved in histidine metabolism being affected, further indicating the effect WB occurrence has on histidine metabolism [ 34 ]. Surprisingly, though, a study feeding high levels of histidine indicated no effects on meat quality, even though a higher level of carnosine was observed [ 42 ].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The main functions of these molecules include maintaining blood volume through colloidal osmotic effects, participating in blood pH maintenance, hormone and drug transport, cellular coagulation, and catalyzing (enzymes) and regulating (hormones) biological processes [75]. Some proteins are also indispensable in inflammatory, immune, and tissue regeneration and repair processes, where they are called acute-phase proteins [59,76].…”
Section: Discussionmentioning
confidence: 99%
“…Khumpeerawat and colleagues reported moderate correlation between CARNS1 levels and carnosine content in chickens, with both having an inverse relationship with bird age 29 . In addition, 3-methyl-histidine was considered a marker for myofibrillar breakdown and found to have high prediction accuracy for WB 32 . Dietary supplementation of betaalanine and histidine led to increased carnosine levels synthesized in both slow and fast-growing chickens 30,33 , which in turn may potentially increase antioxidant capacity 30,33,34 .…”
Section: Histidine Metabolismmentioning
confidence: 99%